Mobile Bike Sharing: Identificação e avaliação das funcionalidades principais de uma aplicação móvel - Francisco Modesto da Silva (2019)
This dissertation aims to study, identify, and evaluate a set of tools for a mobile application dedicated to a bike sharing service in the city of Porto. Bike sharing systems are services that "rent" a bicycle for urban usage over a period of time. With recent technological development, bike sharing services are starting to get complemented with technological elements, such as mobile applications, that came to effectively improve the communication and service experience. It is essential that these applications offer a set of tools that enhance the experience of this activity and update the present applications, whose adoption grows slowly. Final users are cyclists with a beginner and intermediate level of experience. This study follows a qualitative approach through usability tests of an application prototype. The instruments used are interviews, persona, scenarios, prototype and sessions of usability evaluation. The use of a small sized sample of usability tests, and the time limitations during the practical research did not allow the generalization of the results found. However, the results revealed the most relevant features for bike sharing applications: the location of stations (at the place closest to the user) and payment methods (link of electronic cards). The integration of the features in the applications meets the users' expectations. The integration of users in the different stages of development of a prototype allows the acquisition of results on the design and behavior, identifying anomalies, frustrations and issues in the prototype, such as lack of feedback messages and icons not evident. The lack of digital applications and bike sharing schemes in the city of Porto has limited the sample of participants, which is one of the main reasons most people do not use this type of service. It is important to reform the present programs in Porto and identify new features that can complement the activity of bike sharing.